The Relationship Between Agility; Eye-foot coordination; Leg Muscles Strength and Soccer Dribbling Skills of Football School (SSB) Playerr - Muhammad Imam Alfaroby; Nurhidayat Nurhidayat; Galuh Yuliar Denata (CV. FOUNDAE, 2022)
Lack of good dribbling skills will affect soccer match victory. The researchers aimed to determine the relationship between eye-foot coordination, leg muscle strength, agility, and the dribbling skills of 20 Football School (SSB) players. Research data were collected using the eye-foot coordination test, leg muscle strength test, mobility test, and dribbling skill test. The data was analyzed using the product-moment correlation and multiple linear regression analysis. The results showed a significant relationship between the eye-foot coordination and dribbling skills of SSB players. Also, there was a substantial relationship between leg muscle strength and dribbling skills of SSB players. Furthermore, there was a significant relationship between agility and dribbling skills of SSB players. Lastly, SSB players had a significant relationship between eye-foot coordination, leg muscle strength, agility, and dribbling skills. This study concludes that good dribbling skills become the basic requirement for soccer players.